2022
DOI: 10.3390/toxins14030200
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Endosperm Starch Composition on Maize Response to Fusarium temperatum Scaufl. & Munaut

Abstract: Fusarium temperatum Scaufl. & Munaut is a newly described taxon belonging to the Fusarium fujikuroi species complex (FFSC) and a frequent causative factor of maize ear rot. The aim of the present study was to determine the responses to the disease in maize populations differing in endosperm features that were classified to flint, dent, and a group of plants with intermediate kernel characteristics. In inoculation studies, substantial variation of host response to the fungus was found among the tested maize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 60 publications
3
3
0
Order By: Relevance
“…A major threat to oak trees in both natural and artificial restoration is the fungi of the genus Fusarium, which was one of the most frequently isolated. In artificial restoration, another abundant type is Alternaria (Król et al, 2015), and the same relationship is confirmed by the study of Wit et al (2015). In natural regeneration, the next most abundant type was Trichoderma.…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…A major threat to oak trees in both natural and artificial restoration is the fungi of the genus Fusarium, which was one of the most frequently isolated. In artificial restoration, another abundant type is Alternaria (Król et al, 2015), and the same relationship is confirmed by the study of Wit et al (2015). In natural regeneration, the next most abundant type was Trichoderma.…”
Section: Resultssupporting
confidence: 53%
“…e research in the Oława Forest District confirms the presence of the above Fusarium species on oaks, however, apart from these three, F. sporotrichioides, F. dimerum, F. graminearum, and four species: F. equiseti, F. graminum, F. poae, F. sambucinum in smaller quantities were the most numerous. Fungi of the type Fusarium were isolated, also from diseased oak shoots, in the study of Wit et al (2015), confirming the presence of these pathogens on this tree species. Fungi of the genus F. oxysporum can also be found on other tree species.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In contrast, ZmWAX2 ‐mediated resistance carries no differences in important agronomical traits under normal growth conditions (Figure S7 ) and even remarkedly increases the corn yield upon F. verticillioides stalk rot (Figures 5 and 6 ). Interestingly, we observed that the morphology and arrangement of endosperm starch granules and invasive hyphae of internal F. verticillioides are quite different between the zmwax2 mutant and ZmWAX2 overexpressor seeds (Figure S9 ), which is consistent with a recent report that endosperm starch composition is associated with maize resistance to fungus infection (Wit et al ., 2022 ). Given that ZmWAX2 is a homologue of genes involved in cuticular wax biosynthesis according to phylogenetic analysis (Figure S2 ), we hypothesize that ZmWAX2 confers a durable and broad‐spectrum resistance to multiple fungal pathogens, at least F. verticillioides in maize.…”
Section: Discussionmentioning
confidence: 99%